2013
DOI: 10.1186/1476-4598-12-46
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle-dependent activity of the novel dual PI3K-MTORC1/2 inhibitor NVP-BGT226 in acute leukemia

Abstract: BackgroundDysregulation of the PI3Kinase/AKT pathway is involved in the pathogenesis of many human malignancies. In acute leukemia, the AKT pathway is frequently activated, however mutations in the PI3K/AKT pathway are uncommon. In some cases, constitutive AKT activation can be linked to gain-of-function tyrosine kinase (TK) mutations upstream of the PI3K/AKT pathway. Inhibitors of the PI3K/AKT pathway are attractive candidates for cancer drug development, but so far clinical efficacy of PI3K inhibitors agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 53 publications
3
40
0
Order By: Relevance
“…A dose-dependent reduction in vital OE19 cells after treatment with each compound was found. The most active concentration of BEZ235 was 1 μM, in concordance with prior reports about PI3K-mTORC inhibitors [26,27].…”
Section: Pharmacological Approaches To Enhance Anti-tumor Efficacy Bysupporting
confidence: 88%
“…A dose-dependent reduction in vital OE19 cells after treatment with each compound was found. The most active concentration of BEZ235 was 1 μM, in concordance with prior reports about PI3K-mTORC inhibitors [26,27].…”
Section: Pharmacological Approaches To Enhance Anti-tumor Efficacy Bysupporting
confidence: 88%
“…This is important as such agents inhibit both mTORC1 and mTORC2 complexes and, potentially, other mTOR complexes that may exist but have not been yet identified. Other studies have also described potent anti-leukemic properties of dual PI3K-mTORC1/2 inhibitors, such as NVP-BGT226 (72) and NVP-BEZ235 (73), in AML.…”
Section: Targeting Mapk and Mtor Pathways In Amlmentioning
confidence: 99%
“…Furthermore, the blockade of PI3K/Akt activity in colon cancer cells has shown promising anti-cancer effects (19)(20)(21)(22). Recent studies have demonstrated that the downstream factor of the PI3K/Akt pathway, the mammalian target of rapamycin (mTOR), is a potential therapeutic target in various types of cancer, including non-small cell lung cancer (23) (26), non-Hodgkin's lymphoma (27) and leukemia (28,29). In addition, the activation of the PI3K/Akt pathway has been shown to correlate with a poor prognosis in stage Ⅱ colon cancer, and Akt phosphorylation is a prognostic factor for disease-free survival (30).…”
Section: Introductionmentioning
confidence: 99%